The Inner Ear Heat Shock Transcriptional Signature Identifies Compounds That Protect Against Aminoglycoside Ototoxicity - Ryals, Matthew; Morell, Robert J.; Martin, Daniel; Boger, Erich T.; Wu, Patricia; Raible, David W.; Cunningham, Lisa L. (Frontiers in Cellular Neuroscience, 2018)
Mechanosensory hair cells of the inner ear transduce auditory and vestibular sensory input. Hair cells are susceptible to death from a variety of stressors, including treatment with therapeutic drugs that have ototoxic side effects. There is a need for co-therapies to mitigate drug-induced ototoxicity, and we showed previously that induction of heat shock proteins (HSPs) protects against hair cell death and hearing loss caused by aminoglycoside antibiotics in mouse. Here we utilized the library of integrated cellular signatures (LINCS) to identify perturbagens that induce transcriptional profiles similar to that of heat shock. Massively parallel sequencing of RNA (RNA-Seq) of heat shocked and control mouse utricles provided a heat shock gene expression signature that was used in conjunction with LINCS to identify candidate perturbagens, several of which were known protect the inner ear. Our data indicate that LINCS is a useful tool to screen for compounds that generate specific gene expression signatures in the inner ear. 42 LINCS-identified perturbagens were tested for otoprotection in zebrafish, and three of these were protective. These compounds also induced the heat shock gene expression signature in mouse utricles, and one compound protected against aminoglycoside-induced hair cell death in whole organ cultures of utricles from adult mice.